RELASI ISLAM DAN BUDAYA LOKAL: Studi Tentang Tradisi Nyadran di Desa Sumogawe Kecamatan Getasan Kabupaten Semarang - Kastolani dan Abdullah Yusof (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
This article is the result of research conducted with the aim to find out the views of the community, as well as the impact on the rite procession of nyadran tradition in the village Sumogawe Getasan Semarang. The method used is a qualitative research approach phenomenologis. The subjects were the villagers Sumogawe Getasan Semarang. The results of this study addressed that (1) people’s views make sense of nyadran tradition an expression of socio-religious reflection. For example religious visit to the graves of ancestors as aform of preservation of cultural heritage and the traditions of the ancestors. (2) The process of implementation nyadran rites in the village Sumogawe was three days before before the implementation of nyadran the citizens Sumogawe Getasan held nyekar and traditions manganan (invitation). (3) The impact of nyadran can be perceived by the public as a form Sumogawea remuneration on ancestral sacrifices both material and non-material, to be successful. Nyadran preservation of tradition is a form of preservation of cultural heritage adhiluhung ancestors going back, there is some wisdom in the procession tradition nyadran highly relevant to the present context. Moreover, nyadran transformed into a gathering place.Keywords: Islam, Culture, Nyadran